2018
DOI: 10.1161/jaha.118.008994
|View full text |Cite
|
Sign up to set email alerts
|

Attended and Unattended Automated Office Blood Pressure Measurements Have Better Agreement With Ambulatory Monitoring Than Conventional Office Readings

Abstract: BackgroundAutomated office blood pressure (AOBP) measurement is superior to conventional office blood pressure (OBP) because it eliminates the “white coat effect” and shows a strong association with ambulatory blood pressure.Methods and ResultsWe conducted a cross‐sectional study in 146 participants with office hypertension, and we compared AOBP readings, taken with or without the presence of study personnel, before and after the conventional office readings to determine whether their variation in blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 21 publications
2
34
1
2
Order By: Relevance
“…The authors concluded that unattended and attended office BP measurements are comparable when measurements take place at a familiar general practitioner's office. In another recently published study, in 146 patients, we also found that there was no difference between attended and unattended AOBPs and both were similar to daytime ambulatory BP measurements.…”
Section: Discussionsupporting
confidence: 81%
“…The authors concluded that unattended and attended office BP measurements are comparable when measurements take place at a familiar general practitioner's office. In another recently published study, in 146 patients, we also found that there was no difference between attended and unattended AOBPs and both were similar to daytime ambulatory BP measurements.…”
Section: Discussionsupporting
confidence: 81%
“…Only attrition bias was relevant in 7 studies due to missing data (BP readings missing, patients lost at follow-up). 16 studies compared AOBP with traditional OBP taken by physicians 4,8,10,12,19,[21][22][23][24]27,28,30,[32][33][34]37 ; 16 studies compared AOBP with awake ABPM 4,8,10,18,19,20,22,[24][25][26]29,[33][34][35]37,38 ; AOBP was compared with HBPM in 7 studies 10,12,24,27,28,30,38 and with non-physician OBP in 10 studies 4,8,15,[18][19][20]31,[36][37][38] .…”
Section: Characteristic Of the Included Studiesmentioning
confidence: 99%
“…Recently, AOBP readings have been shown to yield similar values when BP measurements were taken with or without medical staff. These readings were devoid of order effect and were comparable with awake ABP rather than conventional office values . The unattended office BP, however, is a guarantee that talking will be strictly avoided.…”
Section: Factors That Influence Aobp Measurements Are the Followingmentioning
confidence: 55%